2018
DOI: 10.1103/physrevb.98.024427
|View full text |Cite
|
Sign up to set email alerts
|

Electric-field control of spin-wave power flow and caustics in thin magnetic films

Abstract: An external electric field can modify the strength of the spin-orbit interaction between spins of ions in magnetic crystals. This influence leads to a spin-wave frequency shift that is linear in both the applied electric field and the wave vector of the spin wave. Here we study theoretically the external electric field as a means of control of the spin-wave power flow in thin ferromagnets. The spin-wave group velocity and focusing patterns are obtained from the slowness (isofrequency) curves by evaluating thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 32 publications
1
17
0
Order By: Relevance
“…(ii) The spin-wave wavelength conversion (albeit probably not the Möbius mode formation) should occur in magnonic systems featuring a single valley at a finite wave number, with the shift induced, e.g., by the Dzyaloshinskii-Moriya interaction (DMI) interaction [55] or electric field [56].…”
Section: Discussionmentioning
confidence: 99%
“…(ii) The spin-wave wavelength conversion (albeit probably not the Möbius mode formation) should occur in magnonic systems featuring a single valley at a finite wave number, with the shift induced, e.g., by the Dzyaloshinskii-Moriya interaction (DMI) interaction [55] or electric field [56].…”
Section: Discussionmentioning
confidence: 99%
“…However, the desired nonuniformity in magnetization can be created through proper design of sample structure by using single or multiple magnetic materials, and can be controlled through dynamic demagnetizing field with the help of an external magnetic field 81 . Very recently, the theoretical work by Krivoruchko et al have shown that an external electric field, applied along a direction perpendicular to SW wavevector and magnetization, can induce Dzyaloshinskii-Moriya-like (DM-like) interaction 82 , known as Aharanov-Casher effect. This electric field-induced DM-like interaction makes SWdispersion anisotropic and nonreciprocal, which also promises to be a potential method to create caustic-like SW beam excited from a point source in a FM thin film.…”
Section: Formation Of Reconfigurable Sw Nanochannelsmentioning
confidence: 99%
“…Although there are some reports about the electric-field modulation of SWs in multiferroic materials 27,28 and ferrimagnetic insulators (e.g. YIG) 82,86 , the VCMA modulation of SWs in metallic FMs has several advantages over them as already discussed.…”
Section: Reconfigurable Magnonic Crystalsmentioning
confidence: 99%
See 1 more Smart Citation
“…A plethora of theoretical and experimental investigations have demonstrated the electric field–induced control of magnetization in magnetic heterostructures including multiferroic materials ( 19 ), FM semiconductors ( 20 ), piezoelectric materials ( 21 ), or metallic FM/insulator (oxide) interfaces ( 22 ). Furthermore, parametric pumping of SWs by means of VCMA ( 23 ) and electric field control of SW power flow and caustics in thin magnetic films have also been demonstrated theoretically ( 24 ). FM/oxide interfaces have gained a substantial attention due to their superior control over magnetic parameters (e.g., anisotropy) at ambient condition as compared to other systems.…”
Section: Introductionmentioning
confidence: 99%